An Analysis of Factors Influencing Low Critical Thinking Skills among University Students in Learning (Wiyatamandala, 2025)
This systematic literature review aims to analyze the major contributing factors influencing the low level of critical thinking skills among university students in academic learning environments. Using the PRISMA methodology, a total of 15 articles published from 2019 to 2024 were selected through Scopus, ERIC, ResearchGate, and national academic databases. The results show that the low integration of active learning methods, limited assessment for higher-order thinking, socio-cultural inhibitions, lack of instructional innovation, and psychological blocks such as anxiety or low motivation significantly reduce students' critical thinking capacity. Implications for future instructional design, pedagogical practices, and institutional policy are discussed.